Cover Image, Volume 117, Number 11, November 2016. Issue 11 (November 2016) - Legartová, Soňa; Sehnalová, Petra; Malyšková, Barbora; Küntziger, Thomas; Collas, Philippe; Cmarko, Dušan; Raška, Ivan; Sorokin, Dmitry V.; Kozubek, Stanislav; Bártová, Eva
Abstract : Cover : The cover image, by Eva Bártová et al., is based on the Article Localized Movement and Levels of 53BP1 Protein Are Changed by γ‐irradiation in PML Deficient Cells, DOI:10.1002/jcb.25551 .